Deriving a theory of learning from social movement practices - Mai Atta; John Holst (European Journal for Research on the Education and Learning of Adults)
The field of Adult Education is rich with general theories of learning but limited in terms of theories that inform social movement learning (SML). Today, there are several conceptualizations of SML, but little learning theory development based directly on empirical studies of SML. This article aims to present findings from a systematic literature review of empirical studies on social movement learning (SML). We collected and identified 69 empirical studies focusing on adult learning and education within social movements for this literature review. We purposely focused on empirical research studies and did not include works that conceptualise or theorise social movement learning outside of actual empirical studies of SML. From our review of empirical studies, we have identified five elements we believe could serve as the foundation of a theory of learning and education in social movements.